Oral microbiome in Proliferative Verrucous Leukoplakia exhibits loss of diversity and enrichment of pathogens. (September 2021) - Herreros-Pomares, Alejandro; Llorens, Carlos; Soriano, Beatriz; Zhang, Feiyu; Gallach, Sandra; Bagan, Leticia; Murillo, Judith; Jantus-Lewintre, Eloísa; Bagan, José
Graphical abstract: Highlights: Oral microbial dysbiosis is a common state in patients with PVL. PVL patients show a general loss of diversity (OTUs) compared to healthy donors. Protumorigenic pathogens, like Campylobacter jejuni, were found in PVL patients. Abstract: Objectives: Oral microbiome plays an important role in oral diseases. Among them, proliferative verrucous leucoplakia (PVL) is an uncommon form of progressive multifocal leukoplakia with a worryingly rate of malignant transformation. Here, we aimed to characterize the oral microbiome of PVL patients and compare it with those of healthy controls. Material and methods: Oral biopsies from ten PVL patients and five healthy individuals were obtained and used to compare their microbial communities. The sequence of the V3-V4 region of 16S rRNA gene was used as the taxonomic basis to estimate and analyze the composition and diversity of bacterial populations present in the samples. Results: Our results show that the oral microbial composition and diversity are significantly different among PVL patients and healthy donors. The average number of observed operational taxonomic units (OTUs) was higher for healthy donors than for PVL, proving a loss of diversity in PVL. Several OTUs were found to be more abundant in either group. Among those that were significantly enriched in PVL patients, potential protumorigenic pathogens like Oribacterium sp. oral taxon 108, Campylobacter jejuni, uncultured Eubacterium sp., Tannerella, and Porphyromonas were identified. Conclusion: Oral microbiome dysbiosis was found in patients suffering from PVL. To the best of our knowledge, this is the first study investigating the oral microbiome alterations in PVL and, due to the limited number of participants, additional studies are needed. Oral microbiota-based biomarkers may be helpful in predicting the risks for the development of PVL.